Founder Mutation in N Terminus of Cardiac Troponin I Causes Malignant Hypertrophic Cardiomyopathy - Akl C. Fahed (11514346) (2020)
Background Cardiac troponin I (TNNI3) gene mutations account for 3% of hypertrophic cardiomyopathy and carriers have a heterogeneous phenotype, with increased risk of sudden cardiac death (SCD). Only one mutation (p.Arg21Cys) has been reported in the N terminus of the protein. In model organisms, it impairs PKA (protein kinase A) phosphorylation, increases calcium sensitivity, and causes diastolic dysfunction. The phenotype of this unique mutation in patients with hypertrophic cardiomyopathy remains unknown. Methods We sequenced 29 families with hypertrophic cardiomyopathy enriched for pediatric-onset disease and identified 5 families with the TNNI3 p.Arg21Cys mutation. Using cascade screening, we studied the clinical phenotype of 57 individuals from the 5 families with TNNI3 p.Arg21Cys-related cardiomyopathy. We performed survival analysis investigating the age at first SCD in carriers of the mutation. Results All 5 families with TNNI3 p.Arg21Cys were from South Lebanon. TNNI3 p.Arg21Cys-related cardiomyopathy manifested a malignant phenotype—SCD occurred in 30 (53%) of 57 affected individuals at a median age of 22.5 years. In select carriers without left ventricular hypertrophy on echocardiogram, SCD occurred, myocyte disarray was found on autopsy heart, and tissue Doppler and cardiac magnetic resonance imaging identified subclinical disease features such as diastolic dysfunction and late gadolinium enhancement. Conclusions The TNNI3 p.Arg21Cys mutation has a founder effect in South Lebanon and causes malignant hypertrophic cardiomyopathy with early SCD even in the absence of hypertrophy. Genetic diagnosis with this mutation may be sufficient for risk stratification for SCD. Other Information Published in: Circulation: Genomic and Precision Medicine License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1161/circgen.120.002991